REINTERPRETATION OF ECOLOGICAL VERSES TO IMPLEMENT ECO-ETHICS IN ISLAMIC EDUCATION - Al Walidah, Iffah; Husaini, Irpan (Jurnal Tatsqif, 2023)
Modern commentators and intellectuals have begun to explore studies that link the position of humans and plants as a unity of living things created by God's holy creation. Generally, when talking about ecology, humans are used as the main character in caring for nature. Many verses in the Qur’an talk about how the human spirit is metaphorized with ecological elements. As a religious principle, Islam describes monotheism as a syajarah thayyibah whose roots reach the ground and its branches reach the sky (QS: 14:24). This research is qualitative descriptive-analytical research. Researchers will collect data related to this research. Furthermore, the data was analyzed to find a solution with the Maqashidi Interpretation method then relate it to how ecological ethics lives in Islamic education. This research focuses on QS. Al-Fatihah: 1 and Ar-Rum: 30. The result of this research show that the redaction of rabb al-'alamin in QS. Al-Fatihah shows the closeness between Rabb and 'alamin. On the other hand, the Qur’an explains that natural damage occurs due to human activities (QS.30:41). The implied meaning in the two verses is that humans, nature, and other creatures need each other and are encouraged to respect each other. An understanding of comprehensive ecological verses will have a good effect on ecological ethics in the world of Islamic education. The educational process provides knowledge about how nature works and how to interact with the natural world. The growing eco-Islamic movement utilises Islamic educational institutions, both traditional and modern as centres of environmental learning and teaching. The Islamic educational landscape remains essential in broadcasting environmental narratives that present ethical and educational visions relevant to contemporary ecological movements.